Consumer perception of situational appropriateness for fresh, dehydrated and fresh-cut fruits. (February 2021) - Tarancón, P.; Fernández-Serrano, P.; Besada, C.
Graphical abstract: Highlights: Situational appropriateness (SA) of different fruit types was investigated. SA of fresh fruit depended on fruit size, cutlery need, and spoilage susceptibility. Dehydrated and fresh-cut fruits were convenient to be eaten in contexts out of home. Organoleptic properties are the main consumption barrier of dehydrated fruit. Price, nutritional concerns and plastic packaging are barriers to consume fresh-cut fruit. Abstract: In recent years, a decreasing trend in fruit consumption has been detected in Mediterranean countries, with the consequent risk for the population's health. The objective of this study was to obtain consumer knowledge that can be useful to promote fruit consumption by designing specific interventions. This study was conducted in Spain as its inhabitants have traditionally adhered to the Mediterranean diet. Firstly, four fresh fruit types were identified based on the consumer perception of the fruit characteristics that condition the eating process (fruit size, the need for cutlery to peel/eat fruit, and susceptibility to be spoiled during transportation). Then consumer perception of situational appropriateness of six different fruit types (the 4 types of fresh fruit previously identified, dehydrated non-traditional fruit (DF), and fresh-cut fruit ready to eat on the go (FCF)) was investigated by the Item-By-Use method using Check-All-That Apply (CATA) questions. The potential of DF and FCF to broaden fruit consumption situations, and barriers for their consumption, were evaluated. Fresh fruits, particularly 'easy-to-peel' ones like mandarins or bananas, were those preferred by consumers in most evaluated contexts. DF were considered mainly appropriate to be consumed 'As an ingredient' and 'As a healthy snack', while FCF were more suitable 'To be included in school lunchboxes' and 'To eat immediately'. According to our results, these two processed fruit types can help to increase the fruit consumption of a non-negligible percentage of the population (38% of participants), but it is necessary to overcome the barriers related mostly to sensory properties, plastic packaging and consumer misperception of fewer healthy properties compared to fresh fruit.